Assessing ecotourism natural attractions, facilities and activities in Bako National Park - Noorfaseha, Binti Safhee (Universiti Malaysia Sarawak (UNIMAS), 2012)
Tourism is one of the fastest growing industries in the world (Newsome et al., 2002). According to Mathieson and Wall (1982), tourism is the temporary movement of people to destinations outside their normal home and workplace, the activities undertaken during the stay and the facilities created to cater for their needs. Along with its phenomenal growth and size, tourism is also responsible for extensive impacts on economy, environment, and impact on society and on cultural sites (Newsome et al., 2002). Tourism sector in Malaysia has been recognized by the government as a major source of revenue and act as catalyst for the country’s economic renaissance. According to Tourism Minister Datuk Seri Dr. Ng Yen Yen, in year 2011, the tourist arrivals increased to 24.7 million compared to 24.6 million in 2010 while receipts increased by RM1.8 billion to RM58.3 billion compared to RM56.5 billion for the previous year (Ho, 2012).